Exercise and eating habits among urban adolescents: a cross-sectional study in Kolkata, India - Soumitra Kumar; Saumitra Ray; Debabrata Roy; Kajal Ganguly; Sibananda Dutta; Tanmay Mahapatra; Sanchita Mahapatra; Kinnori Gupta; Kaushik Chakraborty; Mrinal Kanti Das; Santanu Guha; Pradip K. Deb; et al. (BMC, 2017)
Abstract Background Unhealthy eating and lack of exercise during adolescence culminated into earlier onset and increasing burden of atherosclerotic cardiovascular diseases (CVDs) worldwide. Among urban Indian adolescents, prevalence of these risk factors of CVD seemed to be high, but data regarding their pattern and predictors was limited. To address this dearth of information, a survey was conducted among urban adolescent school-students in Kolkata, a highly populated metro city in eastern India. Methods During January-June, 2014, 1755 students of 9th-grade were recruited through cluster (schools) random sampling. Informed consents from parents and assents from adolescents were collected. Information on socio-demographics, CVD-related knowledge and perception along with eating and exercise patterns were collected with an internally validated structured questionnaire. Descriptive and regression analyses were performed in SAS-9.3.2. Results Among 1652 participants (response rate = 94.1%), about 44% had poor overall knowledge about CVD, 24% perceived themselves as overweight and 60% considered their general health as good. Only 18% perceived their future CVD-risk and 29% were engaged in regular moderate-to-vigorous exercise. While 55% skipped meals regularly, 90% frequently consumed street-foods and 54% demonstrated overall poor eating habits. Males were more likely to engage in moderate-to-vigorous exercise [adjusted odds ratio (AOR) = 3.40(95% confidence interval = 2.55-4.54)] while students of higher SES were less likely [AOR = 0.59(0.37-0.94)]. Males and those having good CVD-related knowledge were more likely to exercise at least 1 h/day [AOR = 7.77(4.61-13.07) and 2.90(1.46-5.78) respectively]. Those who perceived their future CVD-risk, skipped meals more [2.04(1.28-3.25)] while Males skipped them less [AOR = 0.62(0.42-0.93)]. Subjects from middle class ate street-foods less frequently [AOR = 0.45(0.24-0.85)]. Relatively older students and those belonging to higher SES were less likely to demonstrate good eating habits [AOR = 0.70(0.56-0.89) and 0.23(0.11-0.47) respectively]. A large knowledge-practice gap was evident as students with good CVD-related knowledge were less likely to have good eating habits [AOR = 0.55(0.32-0.94)]. Conclusions CVD-related knowledge as well as eating and exercise habits were quite poor among adolescent school-students of Kolkata. Additionally, there was a large knowledge-practice gap. Multi-component educational interventions targeting behavioral betterment seemed necessary for these adolescents to improve their CVD-related knowledge, along with appropriate translation of knowledge into exercise and eating practices to minimize future risk of CVDs.